2024
DOI: 10.1021/acs.jpclett.4c00494
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Kinetic Studies of OH + HO2 Radical–Radical Reaction through Direct Measurement of Precursor and Radical Concentrations with High-Resolution Time-Resolved Dual-Comb Spectroscopy

I-Yun Chen,
Che-Wei Chang,
Christa Fittschen
et al.

Abstract: The radical−radical reaction between OH and HO 2 has been considered for a long time as an important reaction in tropospheric photochemistry and combustion chemistry. However, a significant discrepancy of an order of magnitude for rate coefficients of this reaction is found between two recent experiments. Herein, we investigate the reaction OH + HO 2 via direct spectral quantification of both the precursor (H 2 O 2 ) and free radicals (OH and HO 2 ) upon the 248 nm photolysis of H 2 O 2 using infrared two-colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…We note that in 2023 Speak et al reported a value of k 9 about 11 times lower than the current IUPAC recommendation of 1.1 × 10 –10 cm 3 ·molec –1 ·s –1 . However, a 2024 study by Chen et al confirmed the previous consensus, and we view k 9 = 1.1 × 10 –10 cm 3 ·molec –1 ·s –1 as reliable. Our modeled OH decays are thus sensitive only to the initial radical concentrations, providing an opportunity to confirm these expected concentrations by kinetic fits.…”
Section: Resultssupporting
confidence: 73%
“…We note that in 2023 Speak et al reported a value of k 9 about 11 times lower than the current IUPAC recommendation of 1.1 × 10 –10 cm 3 ·molec –1 ·s –1 . However, a 2024 study by Chen et al confirmed the previous consensus, and we view k 9 = 1.1 × 10 –10 cm 3 ·molec –1 ·s –1 as reliable. Our modeled OH decays are thus sensitive only to the initial radical concentrations, providing an opportunity to confirm these expected concentrations by kinetic fits.…”
Section: Resultssupporting
confidence: 73%